2022
DOI: 10.31234/osf.io/472p5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in inhibition-related brain function and psychological flexibility during smoking abstinence predict longer time to relapse

Abstract: Despite substantial health benefits, smoking cessation attempts have high relapse rates. Neuroimaging measures can sometimes predict individual differences in substance use phenotypes – including relapse – better than behavioral metrics alone. No study to date has compared the relative prediction ability of changes in psychological processes across prolonged abstinence with corresponding changes in brain activity. Here, in a longitudinal design, measurements were made one day prior to smoking cessation, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The same study also noted increased right central P3 (failed stop trials) and decreased frontal and left posterior late P3 (correct stop trials) from T1 to T3 (4 weeks) that predicted longer time to relapse (Lespine et al, 2022 ). However, the study reported that the EEG metrics were weak predictors of time to relapse relative to psychological and affective state variables (Lespine et al, 2022 ).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The same study also noted increased right central P3 (failed stop trials) and decreased frontal and left posterior late P3 (correct stop trials) from T1 to T3 (4 weeks) that predicted longer time to relapse (Lespine et al, 2022 ). However, the study reported that the EEG metrics were weak predictors of time to relapse relative to psychological and affective state variables (Lespine et al, 2022 ).…”
Section: Resultsmentioning
confidence: 85%
“…The same study also showed trends for associations of smaller Pe with relapse as well as lower ERN with smoking behavior. A third report, using a stop-signal task, indicated faster left fronto-central N2 latency, higher fronto-lateral P3, and lower left central and right frontal P3 elicited by correct stop trials at T1 (pre-quit baseline) predicted longer time to relapse over a year (Lespine et al, 2022 ). The same study also noted increased right central P3 (failed stop trials) and decreased frontal and left posterior late P3 (correct stop trials) from T1 to T3 (4 weeks) that predicted longer time to relapse (Lespine et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation